Epidemiological investigation of euthanasia in an Ontario animal shelter. Issue 6 (June 2018) - Mozes, Rachael; Pearl, David L; Niel, Lee; Weese, J Scott
Objectives: The objective was to evaluate factors associated with euthanasia in an animal shelter in Kitchener-Waterloo, Ontario, Canada. Methods: Data from 3737 cats admitted to the shelter between January and December 2011 were evaluated. Results: Overall, 1989/3737 (53%) of admitted cats were euthanized. Male cats had greater odds of being euthanized than females (odds ratio [OR] 1.63, 95% confidence interval [CI] 1.29–2.05; P <0.001) and surrendered cats were more likely to be euthanized than strays (OR 38.0, 95% CI 14.8–97.69; P <0.001). Black cats were more likely to be euthanized than cats of another color (OR 1.45, 95% CI 1.16–1.80; P <0.001). Cats that spent >5 days in the shelter were more likely to be euthanized than those that spent <5 days in the shelter (OR 1.57, 95% CI 1.25–1.97; P <0.001). Cats that spent >20 days in the shelter were less likely to be euthanized than those that spent <5 days in the shelter (OR 0.26, 95% CI 0.19–0.34; P <0.001). Age, an age quadratic term, neuter status and interactions among these variables were statistically significant; the odds of unneutered animals being euthanized was high and relatively stable across age groups, but in neutered animals the odds of being euthanized increased with age before plateauing in older cats. Conclusions and relevance: With >50% of the cats admitted to the shelter in 2011 euthanized, it is important to understand the contributing risk factors that predispose shelter cats to euthanasia and what changes can be made to the shelter system and in owner education to lower the incidence of euthanasia.